Hyperthermic Oncology from Bench to Bedside - Kokura, Satoshi; Yoshikawa, Toshikazu; Ohnishi, Takeo (Springer Nature Singapore : Imprint: Springer, 2016)
This comprehensive work broadens readers' understanding of the rudimentary mechanism of the anti-cancer effect of hyperthermia. It also presents state-of-the-art clinical outcomes by hyperthermia treatment of cancer. In the past few decades, basic and clinical research have shown through in vitro experiments that hyperthermia inhibits epithelial-mesenchymal transition (EMT), resulting in the prevention of metastasis. It also has been learned that hyperthermia shows its superior benefit when applied in combination with radiation therapy, chemotherapy, or various immunotherapies as treatments of several types of carcinoma. The chapters here from expert contributors describe the details of their research for each type of cancer. This book provides not only an overview and the current status of hyperthermia but also its future perspectives. Therefore this volume will greatly benefit oncologists, radiologists and radiology technologists, and chemotherapists who are involved in immunotherapy for all kinds of cancer.